Surface Chemistry in Cobalt Phosphide-Stabilized Lithium–Sulfur Batteries - Zhong, Yiren; Yin, Lichang; He, Peng; Liu, Wen; Wu, Zishan; Wang, Hailiang (Journal of the American Chemical Society, 2018)
Chemistry at the cathode/electrolyte interface plays an important role for lithium–sulfur batteries in which stable cycling of the sulfur cathode requires confinement of the lithium polysulfide intermediates and their fast electrochemical conversion on the electrode surface. While many materials have been found to be effective for confining polysulfides, the underlying chemical interactions remain poorly understood. We report a new and general lithium polysulfide-binding mechanism enabled by surface oxidation layers of transition-metal phosphide and chalcogenide materials. We for the first time find that CoP nanoparticles strongly adsorb polysulfides because their natural oxidation (forming Co–O–P-like species) activates the surface Co sites for binding polysulfides via strong Co–S bonding. With a surface oxidation layer capable of confining polysulfides and an inner core suitable for conducting electrons, the CoP nanoparticles are thus a desirable candidate for stabilizing and improving the performance of sulfur cathodes in lithium–sulfur batteries. We demonstrate that sulfur electrodes that hold a high mass loading of 7 mg cm–2 and a high areal capacity of 5.6 mAh cm–2 can be stably cycled for 200 cycles. We further reveal that this new surface oxidation-induced polysulfide-binding scheme applies to a series of transition-metal phosphide and chalcogenide materials and can explain their stabilizing effects for lithium–sulfur batteries.